Cinema and Special Education: Debates on gender and inclusion through the Percy Jackson series (Revista Apotheke, 2025)
The present text corresponds to the experiences carried out with students from the Special Education program through a Visual Arts course. The discussion is based on the Educational Perspective of Visual Culture (Hernández, 2000), with the aim of fostering discussions through artistic proposals triggered by images from cinema. Through this approach, dialogues were initiated around gender and inclusion issues (Louro, 2013) among pre-service teachers in the Special Education program. The results highlight the importance of bringing works like Percy Jackson into the classroom, especially in the context of inclusive education, as educators can thus stimulate discussions about diversity, showing that individual differences can, in fact, be one’s greatest strengths. In this way, cinema becomes a bridge between fiction and reality, promoting reflection, belonging, and inclusion in the training of education professionals.
Keywords: visual culture; cinema; special education; arts